Brachythecium glareosum (Bruch ex Spruce) Schimp. türünün fitokimyasal profillemesi ve in silico destekli antifungal potansiyelinin ön değerlendirmesi - Çambay, Zafer; Uslu, Harun; Bayçinar, Kevser Özdemir; Göktaş, Bünyamin; Güngören, Muhammed; Alataş, Mevlüt (Çankırı Karatekin Üniversitesi, 2025)
Bu çalışma, Brachythecium glareosum (Bruch ex Spruce) Schimp.'un fitokimyasal bileşenlerini ve farmakolojik potansiyelini araştırmayı, biyoaktif potansiyellerini anlamayı ve briyofit türevi doğal ürünlerle ilgili gelecekteki araştırmaları teşvik etmeyi amaçlamaktadır. Ayrıca, fitokimyasal ve biyoaktivite açısından B. glareosum üzerine yapılan ilk çalışmalardan biri olmayı hedeflemektedir. HPLC analizi, B. glareosum özütünün bazı fenolik bileşiklerinin tespitini ortaya koymuştur. Bazı fenolik bileşiklerin in silico antifungal potansiyeli ortaya çıkarılmıştır. 2,5-Dihidroksibenzoik asit ve 3,4-Dihidroksibenzoik asit bileşiklerinin, Mycobacterium tuberculosis'in Sitokrom P450 14Alfa-Sterol Demetilaz'ını (Cyp51) mikromolar düzeyde inhibe ettiği hesaplanmıştır. Bu çalışma, B. glareosum'un fenolik profilinin daha geniş analitik tekniklerle genişletilmesinin terapötik açıdan önemli ek biyoaktif bileşikleri ortaya çıkarabileceğini öne sürmektedir. İn siliko tahminlerle belirtilen antifungal aktiviteyi doğrulamak için daha fazla biyolojik analiz yapılması gerekmektedir.

Phytochemical studies show that mosses can produce a range of bioactive chemicals that enhance defense mechanisms and ecological resilience. This study aims to investigate the phytochemical constituents and pharmacological potential of Brachythecium glareosum (Bruch ex Spruce) Schimp. to understand their bioactive potential and to stimulate future research into bryophyte-derived natural products. It also aims to be one of the first studies on B. glareosum in terms of phytochemicals and bioactivity. HPLC analysis revealed the presence of several phenolic compounds in the extract of B. glareosum. The study revealed the in silico antifungal potential of some phenolic compounds. It has been calculated that 2,5-Dihydroxybenzoic acid and 3,4-Dihydroxybenzoic acid compounds will inhibit Cytochrome P450 14Alpha-Sterol Demethylase (Cyp51) of Mycobacterium tuberculosis at the micromolar level. The study suggests that using more advanced methods to analyze B. glareosum could help find more useful compounds that can be used for treatment. Further biological assays are warranted to validate the antifungal activity indicated by in silico predictions.
Phytochemical profiling of Brachythecium glareosum (Bruch ex Spruce) Schimp. and preliminary in silico assessment of antifungal potential
Keywords: Botany (Other); Bitki Bilimi (Diğer)